Plant species composition and diversity in traditional agroforestry landscapes on Siberut Island, West Sumatra, Indonesia - GUSMARDI INDRA; ERIZAL MUKHTAR; SYAMSUARDI SYAMSUARDI; CHAIRUL CHAIRUL; MANSYURDIN MANSYURDIN (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Indra G, Mukhtar E, Syamsuardi, Chairul, Mansyurdin. 2024. Plant species composition and diversity in traditional agroforestry landscapes on Siberut Island, West Sumatra, Indonesia. Biodiversitas 25: 1286-1296. The research conducted on Siberut Island, situated in the western part of Sumatra, focuses on traditional communities practicing an agroforestry land management system. This study aimed to identify the plant species within agroforestry land, their respective uses, and techniques for adapting these species to the landscape in two villages, Matotonan in South Siberut District and Bojakan in North Siberut District, Mentawai Islands. Data collection involved direct observation, unstructured interviews for plant species utilization, and transects with a 10m width along contour lines for landscape data. The findings revealed that Siberut's traditional agroforestry land, known as "Pomunean," is divided into Tinugglu and Mone categories based on land slope, proximity to riverbanks, and planted species. Plant species in agroforestry land served nine primary purposes, including staple and additional food, construction, furniture, medicine, firewood, traditional rituals, and commercial activities. Tinugglu land exhibited a higher Landscape Utilization Value Index (LUVI) at 57% compared to Mone land (43%). Regarding specific plant types, Metroxylon sago (Bojakan) and Durio zybethinus (Matotonan) had the highest LUVI values. These findings shed light on the vital role that traditional ecological knowledge and sustainable land management play in maintaining the delicate balance between human livelihoods and the preservation of natural ecosystems.